(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The aim of the current research is to identify the attitudes of mathematics teachers towards the professional standards for teachers in the Kingdom of Saudi Arabia and to identify the significance of the differences between their attitudes according to the variables of gender, years of experience, and academic qualification. To achieve this goal, a questionnaire was prepared including the three main domains, and each domain includes general standards, from which a set of sub-standards emerges, in order to comply with the list of the professional standards. The research sample consisted of (58) male and female mathematics teachers, and the results of the research showed that the attitudes of mathematics teachers towards the professional standards were very high in the three main domains. The results also showed that there were no statistically significant differences between the attitudes of mathematics teachers according to the variables of gender, academic qualification, and years of experience.